Realizing social justice: in theory and practice - Mohd, Mahyudi; Shafinah, Rahim (2022)
This conceptual paper aims to lay down the broad discourse on the notion of justice (al-adl) that is central in ensuring the achievement of the objectives of Shariah in an Islamic moral economy. The Holy Quran repeatedly mentions justice alongside the concepts of truth (al-haqq) and equity (al-qist); highlighting the epistemological imperative for economic agents to practically uphold justice and fairness as a cardinal virtue. To that end, this paper tries to recollect, refine and restore key justice related literatures (in English) as an attempt to bridge the views amongst Islamic scholars to the on-going efforts to establish socio-economic justice in Malaysia. This paper’s discussions could motivate attempts that seek to operationalize the teachings of Islam as they shed light on possible ways for Islamic economists to continue the tradition of designing public policies that are inspired by available ideas within the Islamic heritage.